Martial Law, nationalist education and counter-consciousness experiences of journalists from the field to academe - De Leon, Richard San Miguel 1998-
This study explores how the Marcosian Martial Law regime (1972-1986) shaped the experiences of journalists who eventually taught journalism in the academe. In the body of studies about journalists during Martial Law, there remains a research gap on the experiences of journalists who taught journalism. Their recollections and reflections may still be lingering in the consciousness and memories of these journalist-educators. They are, at once, practitioners and educators who can influence the views of their audience and their students, respectively. The conditions that shaped their consciousness during Martial Law endure and resurge under the present regime of Pres. Rodrigo R. Duterte. When dictator Ferdinand E. Marcos declared Martial Law in 1972, journalists were subjected to various forces such as psychological duress, military invitations, arrest and detention, suspension or forced resignation, torture and death, unemployment or displacement due to closing down of publications, deportation or exile, libel cases, and corruption. These conditions gave birth to journalists who worked either for the crony press of the alternative newspapers. This study accounts for the experiences of 11 Martial Law print journalists who became journalism educators (retired or presently teaching). This study uses an in-depth interview methodology, guided by Renato Constantino's Counter-Consciousness and National Education frameworks and Paulo Freire's Pedagogy of the Oppressed. The journalist-educators exemplified their praxis of nationalist journalism education through transparency and the sharing of experiences, view and treatment about the history of Martial Law, and discussion of journalism principles, ethics and skills in light of social issues and press freedom. Through this education, they were able to develop and propagate a counter-consciousness is characterized by their view of themselves and the world as journalism-educators, their acknowledgment of the need for social change, and their own visions of the press' independent from political, economic, legal and cultural constraints. These findings present journalism education institutions to improve the teaching of journalism as historical repositories of individual and collective memory.